Mapping the Field: Examining the Recertification of Internationally Educated Teachers - Marom, Lilach (Canadian Journal of Education/Revue canadienne de l'éducation, 2017)
In this article I examine the structural barriers in the recerti cation trajectory of internationally educated teachers (IETs) in British Columbia (BC). By applying the Bourdieuian concept of field, I extend from IETs’ experiences in the recertification process to institutional and political factors that affect these experiences. I demonstrate how policies and regulations that govern the field as well as the interplay between its main institutional players, namely, the Teacher Regulation Branch, teacher education programs, and school districts, result in unequal opportunities for IETs to be certified and hired as teachers. As a result, IETs’ potential contribution to diversifying the teacher force in BC is diminished.